Since
, we can rewrite the integral as

Now there is no ambiguity about the definition of f(t), because in each integral we are integrating a single part of its piecewise definition:

Both integrals are quite immediate: you only need to use the power rule

to get
![\displaystyle \int_0^11-3t^2\;dt = \left[t-t^3\right]_0^1,\quad \int_1^4 2t\; dt = \left[t^2\right]_1^4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nf6xmp8j904djbyc33o5te5136o0p5qwly.png)
Now we only need to evaluate the antiderivatives:
![\left[t-t^3\right]_0^1 = 1-1^3=0,\quad \left[t^2\right]_1^4 = 4^2-1^2=15](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kr3th5ji56r89kc53eltlhkvak893ikcbw.png)
So, the final answer is 15.